Digital Democracy vs Invisible Oppressions of Platform Partners: Critical Understanding of Platform Economy in the Regime of Digital India - Nath, Dipika (Unisia, 2026)
This paper examines the emerging challenges of the digitalized economy with specific reference to ride-hailing and food delivery platform workers in India. It critically analyses the oppressive nature of the platform economy through the lens of worker rights, highlighting how algorithmic control, employment informality, and the absence of social and legal protection shape workers’ everyday experiences. A significant concern addressed in the study is the growing participation of youth in precarious platform work, often at the cost of discontinuing formal education. This trend raises serious long-term implications, including potential skilled labour shortages and increased workforce vulnerability. The paper therefore emphasizes the importance of understanding both the perspectives of young platform workers and the role of the state in regulating platform-based economy. It further interrogates the notion of “digital democracy,” arguing that while platform capitalism promotes economic growth and technological inclusion, it simultaneously fails to ensure democratic rights of the workers. This contradiction is examined through a critical analysis of the Social Security Code and its provisions for platform workers. Methodologically, the study adopts a focused group interviews method, content analysis, and participants observation method. Fieldwork was conducted among the workers of ride-hailing and food delivery platforms in Kolkata, West Bengal and in South Delhi. By foregrounding workers lived experiences, the paper contributes to ongoing debates on platform workers, youth employment, and the limitations of welfare provisions of workers in the digital economy.